Developing text and data mining (TDM) support within a university research library - Lisa Bird; James Barnett (Insights: The UKSG Journal, 2024)
The introduction of the text and data mining (TDM) exception in 2014 led to researchers asking for support from staff within Library Services at the University of Birmingham. An initial involvement with a funded corpus linguistics project fostered an effective partnership between the Copyright and Licensing Team and the University’s Research Infrastructure Team. This case study traces the TDM journey that Library Services has subsequently undertaken. The article will look at how staff in Copyright and Licensing and the Research Skills Team identified the original service gap. It will also look at issues impacting on supporting TDM and the results of a TDM survey that was sent to researchers. It concludes with a reflection on how the service might evolve in the future – from the creation and availability of TDM datasets, to the skills development of both librarians and the university communities they support, and the impact artificial intelligence (AI) developments might have on TDM practices.